2015
DOI: 10.1016/j.invent.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of an internet intervention to address behaviors associated with skin cancer risk among young adults

Abstract: Purpose Skin cancer is the most common cancer in the US, and its incidence is increasing. The major risk factor for skin cancer is exposure to ultraviolet radiation (UV). Young adults tend to expose themselves to large amounts of UV and engage in minimal skin protection, which increases their skin cancer risk. Interventions are needed to address risk behaviors among young adults that may lead to skin cancer. The nternet offers a cost-effective way to widely disseminate efficacious interventions. The current pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…We monitored how easily participants were able to complete tasks including: finding additional information about the creation team under the “about us” section, finding in text citations and corresponding full citations in the reference page, playing videos, completing lesson activities, and completing the lesson summary quiz. At the end of the assessment, participants completed a structured usability interview (Heckman et al, 2015), a system usability scale questionnaire (Brooke, 1996), and an acceptability survey (Heckman et al, 2015). The usability scale ranged from 0 to 100 and a score above 68 indicates above-average usability (Brooke, 1996).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We monitored how easily participants were able to complete tasks including: finding additional information about the creation team under the “about us” section, finding in text citations and corresponding full citations in the reference page, playing videos, completing lesson activities, and completing the lesson summary quiz. At the end of the assessment, participants completed a structured usability interview (Heckman et al, 2015), a system usability scale questionnaire (Brooke, 1996), and an acceptability survey (Heckman et al, 2015). The usability scale ranged from 0 to 100 and a score above 68 indicates above-average usability (Brooke, 1996).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The acceptability score of the web-based intervention consists of three categories: likeability; usefulness; and personal applicability. The score is on a scale of 0–10, with 10 being the most acceptable and 0 being the least acceptable (Heckman et al, 2015). One research staff member, with experience in qualitative data collection, administered a structured interview to access features that the participants found most, and least, helpful.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Heckman [ 45 ] reported that their eHealth initiative was guided by intervention development, assessment guidelines for behavioral therapy, and health communication programs with health literacy best-practice. Utilizing a participatory design appeared to improve the relevance of the eHealth resource by addressing issues of culture, gender, age, and sexuality ( Multimedia Appendix 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Goldenberg [ 42 , 43 ] reported personalization along with interactive functionality promoted ownership for HSU. A majority of projects included both HSU and HSP in participatory methods across different developmental stages from contextual inquiry to summative evaluation of the project [ 28 , 29 , 31 , 34 - 38 , 40 - 43 , 45 - 55 , 58 - 61 , 63 - 67 , 69 ]. Evaluation is an integral part of participatory methodology; however, this was reported inconsistently across the 30 studies ( Multimedia Appendix 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skin type was assessed by asking participants the color of their non-sun-exposed skin (very fair, fair, olive, light brown, medium brown, dark brown, or black) [29]. This item was developed as part of a comprehensive, reliable, and frequently utilized skin cancer risk assessment measure [29][30][31].…”
Section: Methodsmentioning
confidence: 99%